Failure to wean off after a routine total anomalous pulmonary venous connection operation: An uncommon association - Riddhi Dhanak; Vikram Halder; Ritesh Shah; Amit Mishra; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2023)
A 6-month-old infant was operated on for supracardiac total anomalous pulmonary venous connection (TAPVC) with usual anatomy. The vertical vein was ligated. Weaning from bypass was attempted twice but was unsuccessful. Coronary sinus atresia was suspected and identified on the opening of the right atrium. A smooth postoperative course occurred after unroofing the coronary sinus. Coronary sinus atresia should be remembered as an uncommon association with TAPVC.